A study of occupants' satisfaction levels on Green Building - Zhang, Wang Yun Xin (2009)
Green mark scheme was launched in 2005 in Singapore. It set the criteria for developers and builders to invest and construct green buildings. A green building (also called a sustainable building) is an outcome of a design which focuses on increasing the efficiency of resource use — energy, water, and materials — while reducing building impacts on human health and the environment during the building's lifecycle, through better siting, design, construction, operation, maintenance, and removal. The benefits of sustainable building can be classified as tangible and intangible benefits.